Digital Market Transactions And Shariah Compliance: A Case Study Of Cash On Delivery (COD) Practices On Shopee In Indonesia - Irwan Misbach; Mitra Gimin (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This study examines the implementation of Cash-on-Delivery (COD) transactions through the Shopee e-commerce platform in Gowa Regency, Indonesia, from the perspective of Islamic economics and Shariah compliance. The primary motivation of this research is to address the growing tension between technological innovation in digital marketplaces and adherence to Islamic ethical and legal principles. Specifically, the study explores how COD practices are understood and enacted by buyers, sellers, and couriers, and whether these practices align with the requirements of valid contracts (ʿaqd) under fiqh muamalah. Employing a qualitative phenomenological design, data were collected through in-depth interviews, field observations, and document analysis from fifteen participants directly involved in Shopee’s COD system. Thematic analysis was conducted to identify behavioral patterns, perceptions of trust, and instances of contractual ambiguity. The results reveal that while COD is widely preferred by consumers for its perceived safety and convenience, many misunderstand its binding nature, often resulting in unilateral cancellations and financial losses for sellers and couriers. These findings highlight inconsistencies between users’ transactional behavior and Shariah principles of transparency (amanah), risk-sharing, and justice (ʿadl). The study concludes that COD can remain permissible within Islamic jurisprudence if key contractual conditions - clear pricing, mutual consent, and khiyar (right of option) are explicitly upheld during the delivery encounter. It recommends targeted digital literacy initiatives, regulatory oversight, and platform policy reforms to harmonize practical efficiency with ethical accountability. By bridging empirical consumer behavior with Islamic economic jurisprudence, this research contributes to the broader discourse on ethical governance and faith-based digital economy development.